Incidence and Risk Factors of Retinopathy of Prematurity, a 10-year Experience of a Single-center, Referral, Hospital - Kanya Chutasmit (2022)
Objective: To explore the incidence and trend of ROP over the past 10 years. The secondary objective was to identify any association between clinical variables and threshold ROP. Materials and Methods: A cross-sectional, retrospective study of infants with <33 weeks' gestational age (GA) or birth weight (BW) <1,500g were screened for ROP between January 2010 and December 2019 Infants who had threshold ROP, labelled as the T-group, were compared against non-threshold infants (either normal or prethreshold ROP), or the NT-group. Results: Of the 1,247 infants who were screened for ROP, 174 (14%) tested positive for ROP while 26 (2.1%) had threshold ROP. Infants who had ROP had a mean ±standard deviation (SD) GA 27.2 ± 2.2 weeks and 115 (66.1%) were <1000g at birth. Advanced GA was independently associated with lower risk of threshold ROP [adjusted odds ratio (95% confidence interval, CI); 0.71 (0.52, 0.98), p=0.04]. There was no difference in respiratory and hemodynamic outcomes between the T and NT-group, except for longer hospitalization (median [P25, P75]; 121[106.3, 160.5] and 93.5[72.3, 129] days, p=0.003]. Culture-positive septicemia was independently associated with threshold ROP [adjusted odds ratio (95% CI); 4.48 (1.72, 11.68), p=0.002]. Conclusion: The incidence of different stages of ROP in infants was 14% and 2.1% for severe ROP which required treatment. Lower GA and positive-culture septicemia was associated with a higher incidence of severe ROP.